Design and Mathematical Modeling of a Novel Angular Displacement Transformer for Accurate Diagnostics of Angular Displacements (Eurasian Journal of Engineering and Technology, 2026)
This paper investigates the linear and nonlinear distributed-parameter circuits of a new resonant electromagnetic transducer intended for converting motion parameters (displacement and velocity) into electrical signals. It is shown that in the linear distributed-parameter circuit of the transducer, the magnetic flux and magnetic field intensity vary along the length of the circuit according to a nonlinear law; moreover, the degree of this nonlinearity increases with an increase in the attenuation coefficient of the magnetic field along the magnetic circuit. When the distributed-parameter magnetic circuit of the transducer operates in the nonlinear regime, achieving a linear distribution of the working magnetic flux along the circuit length requires that the working air gap between adjacent long ferromagnetic rods vary along the length of the circuit according to a prescribed law. In this case, the magnitude of the variation of the working magnetic flux along the circuit length does not depend on the value of the approximation coefficient characterizing the nonlinearity of the circuit.